Defined astrocytic expression of human amyloid precursor protein in Tg2576 mouse brain - Heiland, Tina (Glia, 2018)
Transgenic Tg2576 mice expressing human amyloid precursor protein (hAPP) with the Swedish mutation are among the most frequently used animal models to study the amyloid pathology related to Alzheimer's disease (AD). The transgene expression in this model is considered to be neuron‐specific. Using a novel hAPP‐specific antibody in combination with cell type‐specific markers for double immunofluorescent labelings and laser scanning microscopy, we here report that—in addition to neurons throughout the brain—astrocytes in the corpus callosum and to a lesser extent in neocortex express hAPP. This astrocytic hAPP expression is already detectable in young Tg2576 mice before the onset of amyloid pathology and still present in aged Tg2576 mice with robust amyloid pathology in neocortex, hippocampus, and corpus callosum. Surprisingly, hAPP immunoreactivity in cortex is restricted to resting astrocytes distant from amyloid plaques but absent from reactive astrocytes in close proximity to amyloid plaques. In contrast, neither microglial cells nor oligodendrocytes of young or aged Tg2576 mice display hAPP labeling. The astrocytic expression of hAPP is substantiated by the analyses of hAPP mRNA and protein expression in primary cultures derived from Tg2576 offspring. We conclude that astrocytes, in particular in corpus callosum, may contribute to amyloid pathology in Tg2576 mice and thus mimic this aspect of AD pathology.